1904
DOI: 10.1002/cber.19040370358
|View full text |Cite
|
Sign up to set email alerts
|

Ueber elektrolytische Reduction der Kohlensäure

Abstract: Ueber die Beziehungen beider Korper k m n ich vorerat nichts Sieheres aussagen; vielleicht ist die griine Form monomolekular. die audere dimolekular.Die stabile, sogenannte violette Modification erhllt man beim Umkrystallisiren des Rohprodnctes aus heisaem Renzol in Form von feinen, zu Kugeln yereinigten Nadelchen, welche eine schwer zu beschreibende, grauviolette Farbe besitzen und bei 126 -1 27O unter Inn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1912
1912
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…47 Therefore, Cu and Zn metals were employed initially, in 1904, as cathodes for the electrochemical reduction of CO 2 . 48 In this first work, Cu, Zn, and amalgamated Cu and Zn-based electrodes were tested for the electroreduction of CO 2 in aqueous NaHCO 3 and K 2 SO 4 solutions. The results showed that the electroplated Cu with amalgamated Zn electrodes exhibited high efficiency for reducing pressurized CO 2 , although the main product obtained was HCOOH.…”
Section: Applied Cathode Materialsmentioning
confidence: 99%
“…47 Therefore, Cu and Zn metals were employed initially, in 1904, as cathodes for the electrochemical reduction of CO 2 . 48 In this first work, Cu, Zn, and amalgamated Cu and Zn-based electrodes were tested for the electroreduction of CO 2 in aqueous NaHCO 3 and K 2 SO 4 solutions. The results showed that the electroplated Cu with amalgamated Zn electrodes exhibited high efficiency for reducing pressurized CO 2 , although the main product obtained was HCOOH.…”
Section: Applied Cathode Materialsmentioning
confidence: 99%
“…Through the usage of different electrodes, faradaic efficiency (electron charge conversion) of up to 100% has been noted in several aqueous reactions. [4][5][6][7] Unfortunately, electrochemistry in aqueous solutions does not always yield pure product, but rather a mixture. Separation of both the anode and cathode in two different solutions is vital because it stops the reversion of products to reactants, specifically if the reactants have lower ground state confirmation energy.…”
Section: Introductionmentioning
confidence: 99%